Screen-printed biochemical sensors for detection of ammonia levels in sweat - Towards integration with vital parameter monitoring sports gear - Oertel, Susanne; Jank, Michael; Frey, Lothar; Hofmann, Christian; Lang, Nadine; Struck, Matthias (9th International Conference on Biomedical Electronics and Devices, BIODEVICES 2016 - Part of 9th International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2016, 2016)
The fabrication of fully screen-printed biochemical sensors employing planar integrated solid state electrodes is described. The sensors are developed to fit wearable devices and target the monitoring of ammonia respectively ammonium levels in sweat. Increased ammonium levels in sweat correlate to physical overstrain of muscles, indicated by the breakdown of proteins in muscle cells. The sensor on flexible foil uses an ion-selective working electrode and a reference electrode for potentiometric measurements of the electromotoric force, EMF. For the ammonium ion-selective electrode a cocktail of nonactin was deposited. The printed sensors were calibrated with ammonium standard solutions at a working range between 10-5 M to 0.1 M which corresponds to the range of physiological levels of ammonium in sweat before and during physical strain. The potentiometric characterization of the ion-selective sensor shows a linear behaviour of the EMF versus pC values with a Nernstian slope of 59.3 mV ± 11.2 mV. The combination of low-cost printed sensors, potentiometric sensing, and the integration with textiles represents a very attractive approach for non-invasive monitoring of individual sports performance to prevent overload during physical training.
Keywords: Ammonia; Biomedical sensor; Biosensor; Exercise; Ion-selective electrode; Screen-printed; Sweat; Wearable device